Implementasi Solar Tracker Tanpa Sensor pada Panel Surya - Romi Fernandes; Muldi Yuhendri (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
Solar power plants are a type of electricity generation from renewable energy sources that are widely developed in Indonesia. The power produced by solar power plants is determined by the temperature and radiation from the sun hitting the surface of the solar panels. The greater the solar radiation on the solar panels, the greater the power produced by the solar panels. The maximum radiation of sunlight can be obtained if the surface of the solar panels is perpendicular to the position of the sun. Therefore, the surface of the solar panel needs to be controlled to match the position of the sun which is always moving. This paper proposes time-based tracking of the sun's position without sensors. Solar tracking system (solar tracker) is implemented with Arduino and Real Time Clock (RTC) DS 3231 as a timer. The test results show that the proposed solar tracker has worked well, where the position of the solar panels can follow the movement of the sun